Polarization gratings and electro-optics of deformed helix ferroelectric liquid crystals - Kiselev, Alexei D.; Pozhidaev, Eugene P.; Chigrinov, Vladimir G.; Kwok, Hoi-Sing (Photonics Letters of Poland, 2011)
Electro-optical properties of deformed helix ferroelectric liquid crystal (DHFLC) cells are studied by using a general theoretical approach to polarization gratings in which the transmission and reflection matrices of diffraction orders are explicitly related to the evolution operator of equations for the Floquet harmonics. DHFLC cells with a subwavelength pitch are found to be optically equivalent to uniformly anisotropic biaxial layers. We calculate the transmittance as a function of the electric field and compare the results with the experimental data. The theoretical and experimental results are found to be in good agreement. Full text: PDF References: T. Todorov, N. Tomova, L. Nikolova, "Polarization holography. 1: A new high-efficiency organic material with reversible photoinduced birefringence", Appl. Optics 23, 4309 (1984). [CrossRef] F. Gori, "Measuring Stokes parameters by means of a polarization grating", Opt. Lett. 24, 584 (1999). [CrossRef] J. Tervo, J. Turunen, "Paraxial-domain diffractive elements with 100% efficiency based on polarization gratings", Opt. Lett. 25, 785 (2000). [CrossRef] G. Cincotti, IEEE Jour. Quant. Electr. 39, 1645 (2003). [CrossRef] S.R. Nersisyan, N.V. Tabiryan, D.M. Steeves, B.R. Kimball, "Optical axis gratings in liquid crystals and their use for polarization insensitive optical switching", Jour. Nonlinear Opt. Phys. Mater. 18, 1 (2009). [CrossRef] L. Nikolova, P.S. Ramanujam, "Polarization Holography". (Cambridge University Press, Cambridge, 2009). [CrossRef] J.N. Eakin, Y. Xie, R.A. Pelcovits, M.D. Radcliffe, G.P. Crawford, "Zero voltage Freedericksz transition in periodically aligned liquid crystals", Appl. Phys. Lett. 85, 1671 (2004). [CrossRef] G.P. Crawford, J.N. Eakin, M.D. Radclie, A. Callan-Jones, R.A. Pelcovits, "Liquid-crystal diffraction gratings using polarization holography alignment techniques", Jour. Appl. Phys. 98, 123102 (2005). [CrossRef] V. Presnyakov, K. Asatryan, T. Galstian, V. Chigrinov, "Optical polarization grating induced liquid crystal micro-structure using azo-dye command layer", Opt. Exp. 14, 10558 (2006). [CrossRef] C. Provenzano, P. Pagliusi, G. Cipparrone, "Highly efficient liquid crystal based diffraction grating induced by polarization holograms at the aligning surfaces", Appl. Phys. Lett. 89, 121105 (2006). [CrossRef] C. Provenzano, P. Pagliusi, G. Cipparrone, "Electrically tunable two-dimensional liquid crystals gratings induced by polarization holography", Opt. Exp. 15, 5872 (2007). [CrossRef] H. Choi, J.W. Wu, "Optical properties of holographically generated twisted nematic liquid-crystal gratings", Jour. Opt. Soc. Am. B 26, 1 (2009). [CrossRef] A.D. Kiselev, V.G. Chigrinov, D.D. Huang, "Photoinduced ordering and anchoring properties of azo-dye films", Phys. Rev. E 72, 061703 (2005). [CrossRef] A.D. Kiselev, "Singularities in polarization resolved angular patterns: transmittance of nematic liquid crystal cells", Jour. Phys.: Condens. Matter 19, 246102 (2007). [CrossRef] A.D. Kiselev, R.G. Vovk, R.I. Egorov, V.G. Chigrinov, "Polarization-resolved angular patterns of nematic liquid crystal cells: Topological events driven by incident light polarization", Phys. Rev. A 78, 033815 (2008). [CrossRef] A.D. Kiselev, E.P. Pozhidaev, V.G. Chigrinov, H.-S. Kwok, arXiv:1011.4415. L.A. Beresnev, V.G. Chigrinov, D.I. Dergachev, E.P. Poshidaev, J. Funfschilling, M. Schadt, "Deformed helix ferroelectric liquid crystal display: A new electrooptic mode in ferroelectric chiral smectic C liquid crystals", Liq. Cryst. 5, 1171 (1989). [CrossRef] V.G. Chigrinov, Liquid crystal devices: Physics and Applications (Artech House, Boston, 1999). I. Abdulhalim, G. Moddel, "Electrically and Optically Controlled Light Modulation and Color Switching Using Helix Distortion of Ferroelectric Liquid Crystals ", Mol. Cryst. Liq. Cryst. 200, 79 (1991). [CrossRef] G. Hedge, P. Xu, E. Pozhidaev, V. Chigrinov, H.S. Kwok, "Electrically controlled birefringence colours in deformed helix ferroelectric liquid crystals ", Liq. Cryst. 35, 1137 (2008). [CrossRef] E. Pozhidaev, S. Pikin, D. Ganzke, S. Shevtchenko, W. Haase, "High frequency and high voltage mode of deformed helix ferroelectric liquid crystals in a broad temperature range", Ferroelectrics 246, 235-245 (2000). [CrossRef] G.B. Cohen, R. Pogreb, K. Vinokur, D. Davidov, "Spatial light modulator based on a deformed-helix ferroelectric liquid crystal and a thin a-Si:H amorphous photoconductor", Appl. Optics 3, 455 (1997). [CrossRef]